Multilingualism at the multiplex: a new audience for screen translation? - O’Sullivan, Carol (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The phenomenon of subtitling as an aesthetic or political choice within a film, rather than a strategy for the transfer of a complete work, merits further examination at a time when filmmakers are increasingly including substantial segments of subtitled dialogue in mainstream films. The potential impact of this trend on an audience assumed to be resistant to screen translation is considerable. Despite important reservations, it is argued here that the growing visibility of translation within mainstream cinema has the potential to create space for certain forms of resistance to the dominance of English in the entertainment market, and promote the development of a ‘multilingual imagination’ in multiplex cinemagoers.